Jeff Noon's "Vurt" A Critical Companion - Wenaus, Andrew C. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book offers an examination of Jeff Noon's iconoclastic debut novel, Vurt (1993). In this first book-length study of the novel, which includes an extended interview with Noon, Wenaus considers how Vurt complicates the process of literary canonization, its constructivist relationship to genre, its violent and oneiric setting of Manchester, its use of the Orphic myth as an archetype for the practice of literary collage and musical remix, and how the structural paradoxes of chaos and fractal geometry inform the novel's content, form, and theme. Finally, Wenaus makes the case for Vurt's ongoing relevance in the 21st century, an era increasingly characterized by neuro-totalitarianism, psychopolitics, and digital surveillance. With Vurt, Noon begins his project of rupturing feedback loops of control by breaking narrative habits and embracing the contingent and unpredictable. An inventive, energetic, and heartbreaking novel, Vurt is also an optimistic and heartfelt call for artists to actively create open futures.
Chapter 1: Introduction -- Chapter 2: Totally Feathered Up in Bottletown: Imagining Manchester -- Chapter 3: Orpheus and His Limbic Decks: Avant-Pulp Bricolage and Rites Of Passage -- Chapter 4: Fractal Narrative and Chaos Theory: The Formal and Thematic Paradox Of Escapism -- Chapter 5: What Literature Thinks: Vurt and Neuroemancipation.
Keywords: Fiction; Literary form; Popular Culture; Popular music; Goth culture (Subculture).; Fiction Literature; Literary Genre; Popular Culture; Popular Music; Gothic Studies